2022
DOI: 10.1111/joim.13488
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial meningitis: Aetiology, risk factors, disease trends and severe sequelae during 50 years in Sweden

Abstract: Background Bacterial meningitis (BM) is a rare but severe infection. Few population‐based studies have characterised BM episodes and sequelae over long periods. Methods This was a population‐based observational cohort study with national coverage, using data on aetiological pathogens, sex, premorbid conditions, steroid pretreatment, severe sequelae and birth, death and diagnosis dates collected from 10,339 patients with BM reported to the National Board of Health and Welfare in Sweden between 1964 and 2014. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Consistently, we found that infants had the highest abundance of pathogenic species and rates of meningitis secondary to H. influenzae , and S. pneumoniae was highest among children <5 years of age ( 49 51 ). Meanwhile, S. pneumoniae was the main causative pathogen identified in all three age categories, and H. influenzae was only identified in infants and preschool children, which was in accordance with a previous Chinese report from Yunnan ( 52 ) and other studies from Sweden ( 53 ), Brazil ( 54 ), and England and Wales ( 55 ) but differed from data collected in mainland China ( 56 ). Most children and adolescents with viral CNS infections can recover completely in ~7 to 10 days without specific treatments ( 9 ).…”
Section: Discussionsupporting
confidence: 86%
“…Consistently, we found that infants had the highest abundance of pathogenic species and rates of meningitis secondary to H. influenzae , and S. pneumoniae was highest among children <5 years of age ( 49 51 ). Meanwhile, S. pneumoniae was the main causative pathogen identified in all three age categories, and H. influenzae was only identified in infants and preschool children, which was in accordance with a previous Chinese report from Yunnan ( 52 ) and other studies from Sweden ( 53 ), Brazil ( 54 ), and England and Wales ( 55 ) but differed from data collected in mainland China ( 56 ). Most children and adolescents with viral CNS infections can recover completely in ~7 to 10 days without specific treatments ( 9 ).…”
Section: Discussionsupporting
confidence: 86%
“…Klebsiella pneumoniae rarely causes community‐acquired CNS infections in most countries, including Japan. 1 , 2 , 3 , 4 , 5 Meningitis due to gram‐negative bacilli, including K. pneumoniae , is uncommon, with only a few cases having been described in a multicenter survey and in a hospital‐based survey undertaken in Japan. 4 , 5 This trend is similar in the United States 1 and in Europe 2 , 3 whereas, in Taiwan, the incidence of community‐acquired bacterial meningitis due to K. pneumoniae has been reported to be high.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 Meningitis due to gram‐negative bacilli, including K. pneumoniae , is uncommon, with only a few cases having been described in a multicenter survey and in a hospital‐based survey undertaken in Japan. 4 , 5 This trend is similar in the United States 1 and in Europe 2 , 3 whereas, in Taiwan, the incidence of community‐acquired bacterial meningitis due to K. pneumoniae has been reported to be high. 8 , 9 This epidemiological difference may be related to the accumulation of cases of hypervirulent K. pneumoniae ( hvKp ) in certain Asian countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations